Carbon Dioxide as Feedstock in Selective Oxidation of Propane. Issue 40 (23rd October 2017) - Kang, Jungshik; Czaja, Andrew D.; Guliants, Vadim V.
Abstract : Carbon dioxide is a promising nonconventional oxidant for catalytic dehydrogenation of lower alkanes to olefins. The lower catalytic activity of CO2 compared to oxygen, which is typically used in oxidative dehydrogenation (ODH), also means that more reactive olefins are less likely to undergo undesirable combustion in the presence of CO2 . Supported vanadia catalysts were synthesized by incipient wetness impregnation of silica supports, and by varying the surface coverage of VO x species by means of sodium on the silica surface, the nature of the catalyst was investigated. Promotion with Na cations significantly improved the dispersion of surface VO x species but resulted in the formation of surface Na metavanadate or another reduced V 3+ /V 4+ phase, which lacked catalytic activity in propane ODH in the presence of CO2 . Abstract : Silica‐supported vanadia catalysts were synthesized, and the surface coverage of VO x species varied by using Na + cations. Promotion with Na + significantly improved the dispersion of VO x species but resulted in the formation of surface Na metavanadate, which lacked catalytic activity in oxidative dehydrogenation of propane with CO2 .